RETROSPECTIVE ANALYSIS OF IMPLANT USAGE IN THE TREATMENT OF PATIENTS WITH DENTAL ARCH DEFECTS - V.M. Luchynskyi (Український стоматологічний альманах, 2025)
Dental implantation is one of the leading methods for restoring dentition. One of the factors influencing the effectiveness of treatment is the presence of concomitant chronic conditions, particularly bone deficiency disorders. The assessment of bone mineral density prior to implantation, especially in older patients, can significantly improve the success rate of dental implant procedures and minimize the risk of complications.